Pastoralism and drought. A case study of the Borana of southern Ethiopia - Donaldson, T.J. (1986)
The Borana pastoralists occupy the savannah region of southern Ethiopia and northern Kenya. Their subsistence depends primarily on milk offtake from their Boran cattle and favourable terms of trade for conversion of cattle to grain. In the drought years of 1984 and 1985, animal productivity decreased and terms of trade worsened, leaving the Borana with a shortfall of food energy. The extent of this shortfall and the contribution made by smallstock, as well as bush foods and blood offtake was recorded. Animal productivity parameters, as affected by the drought, showed an increase in calving interval from 14.5 months to at least 17.3 months, a decrease in calving percentage from 70-80% pre-drought, to 8.7%, and a reduction of mean milk offtake of 65% of pre-drought levels. Cattle mortality rates in the study were recorded at approximately 30% of the total herd. Trials were initiated in treating cattle manure as a survival feed, and the feeding of a molasses and urea mix to mature breeding female cattle was initiated in February 1985, prior to the main rainy season, which showed no advantage in feeding the fortified molasses. Trials involving the supplementation of calves during the drought period showed that calf mortality rates were reduced from 100% to 40% at 120 days of age, and that due to this calf viability, milk offtake can be sustained for longer period. When modelled, this leads to improved rates of herd recovery, after the drought, in terms of cattle numbers and milk offtake. The implications of calf supplementation during more normal years is considered in relation to life time productivity.